Resource scheduling scheme of cloud platform for business support system - Honglei MOU; Bo YANG; Yafei HAO (Dianxin kexue)
In 4G era,the development of new technologies and the great changes in the business model of telecom operators promote the progress of business support system cloudization.In order to improve the efficiency of the operation,the dynamic scheduling of cloud resources was explored.A resource scheduling model was proposed based on four business scenarios.